PROSEDUR DAN STRATEGI PENERJEMAHAN ONOMATOPE BAHASA JEPANG DALAM NOVEL BOTCHAN KARYA NATSUME SOSEKI - Ni Nyoman, Atmi Rahayu (Humanis, 2015)
The title of this research is “A Procedure and Strategy of Japanese Onomatopoeia Translation in Botchan Novel By Natsume Soseki” This research describe the translation procedures and strategies applied in translating Japanese onomatopoeia. The theories used in this research are translation procedures according to Vinay and Darbelnet (2000), Newmark (1988), and translation strategies according to Baker (1992). The data were analyzed with equal method. The results of this research show that from 61 onomatopoeias, 1 onomatopoeia with borrowing procedure, 7 onomatopoeias with transposition/shifts procedure, 7 onomatopoeias with modulation procedure, 3 onomatopoeias with equivalence procedure, 2 onomatopoeias with adaptation procedure, 6 onomatopoeias with synonymy procedure, 9 onomatopoeias with componential analysis procedure, 14 onomatopoeias with reduction procedure, 2 onomatopoeias with expansion procedure, 7 onomatopoeias with paraphrase procedure, and 3 onomatopoeias with couplets procedure. In addition, 1 onomatopoeia is translated with loan word, 45 onomatopoeias are translated by paraphrase using a related word, 1 onomatopoeia is translated by paraphrase using an unrelated word, and 14 onomatopoeias are not translated.
Keywords: onomatopoeia translation, translation procedure, translation strategy